Bola shaxsining kognitiv rivojlanishida raqamli texnologiyalarning ta‘siri - Norbosheva, M.A (SCIENCE and SOCIETY, 2023)
The article discusses foreign approaches to the study of the use of digital devices by preschoolers, com- ments on the possible advantages and dangers of the influence of digital technologies on the cognitive development of pre- schoolers.
Keywords: cognitive development; preschool children; digital technologies; digital activities; digital devices